Preliminary Data on Free Use of Fruits and Vegetables Containing Phenylalanine 76–100 mg/100 g of Food in 16 Children with Phenylketonuria - Pinto, Alex (2023)
Funding Information: A.P. received an educational grant from Cambrooke Therapeutics and grants from Vitaflo International, Nutricia, Merck Serono, Biomarin, Mevalia and Applied Pharma Research to attend scientific meetings. This project is also part of A.P.’s. PhD, which is funded by Vitaflo International. A.D. received research funding from Vitaflo International and financial support from Nutricia, Mevalia and Vitaflo International to attend study days and conferences. J.C.R. was a member of the European Nutritionist Expert Panel (Biomarin), the Advisory Board for Applied Pharma Research, Vitaflo, Synlogic, Biomarin and Nutricia and received honoraria as a speaker from APR, Merck Serono, Biomarin, Nutricia, Vitaflo, Cambrooke, PIAM and Lifediet. S.E. received research funding from Nutricia and financial support from Nutricia and Vitaflo International to attend study days and conferences. C.A. received honoraria from Nutricia and Vitaflo International to attend study days and conferences. A.M. has received research funding and honoraria from Nutricia, Vitaflo International and Biomarin. She is a member of the Advisory Board Element (Danone-Nutricia). The remaining authors do not have any conflicts of interest. The funders had no role in the design of the study; in the collection, analyses, or interpretation of data; in the writing of the manuscript; or in the decision to publish the results. ® Funding Information: We received a National Society for Phenylketonuria (NSPKU) grant for GBP 10,000 to support the costs of this study. Publisher Copyright: © 2023 by the authors.